Analysis of the Preceptors' Role in Holistically Shaping Students' Clinical Competence - Zainaro, M. Arifki; Isnainy, Usastiawaty Cik Ayu Saadiah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
This study examines the effectiveness of preceptor roles in supporting the development of clinical competence among nursing students in Indonesia. The research background highlights the low pass rates of nursing competency examinations, which underscore challenges within the nursing education system and the need for enhanced preceptor guidance. The study aims to analyze the role of preceptors in holistically shaping clinical competence, identify factors affecting the effectiveness of preceptor roles, and explore obstacles encountered in clinical mentoring. The research methodology used surveys and statistical analysis of preceptor evaluation data across several performance components, including evaluation (KPE), planning (KPP), and implementation (KPI). The results indicate that preceptors play a positive role in supporting students' competency development, with high average scores in the KPE component, though differences in evaluation aspects require improvement. Preceptors' Major challenges include limited time, experience constraints, and the lack of clear evaluation guidelines. Supporting factors such as ongoing training, institutional support, and technology use can enhance the quality of mentoring. The implications of this research suggest that by addressing these challenges and leveraging available support factors, preceptors can improve their contribution to holistically shaping students' clinical competence. In conclusion, optimizing the role of preceptors is crucial for supporting the more comprehensive development of clinical competence in nursing students. ABSTRAK: Penelitian ini meneliti efektivitas peran preseptor dalam mendukung pengembangan kompetensi klinis di antara mahasiswa keperawatan di Indonesia. Latar belakang penelitian menyoroti rendahnya tingkat kelulusan ujian kompetensi keperawatan, yang menggarisbawahi tantangan dalam sistem pendidikan keperawatan dan kebutuhan akan bimbingan preseptor yang lebih baik. Penelitian ini bertujuan untuk menganalisis peran preseptor dalam membentuk kompetensi klinis secara holistik, mengidentifikasi faktor-faktor yang mempengaruhi efektivitas peran preseptor, dan mengeksplorasi hambatan yang dihadapi dalam bimbingan klinis. Metodologi penelitian menggunakan survei dan analisis statistik data evaluasi preseptor pada beberapa komponen kinerja, termasuk evaluasi (KPE), perencanaan (KPP), dan pelaksanaan (KPI). Hasil penelitian menunjukkan bahwa preseptor berperan positif dalam mendukung pengembangan kompetensi mahasiswa, dengan skor rata-rata tinggi pada komponen KPE, meskipun terdapat perbedaan dalam aspek evaluasi yang memerlukan perbaikan. Tantangan utama preseptor meliputi keterbatasan waktu, kendala pengalaman, dan kurangnya pedoman evaluasi yang jelas. Faktor pendukung seperti pelatihan berkelanjutan, dukungan institusi, dan penggunaan teknologi dapat meningkatkan kualitas bimbingan. Implikasi dari penelitian ini menunjukkan bahwa dengan mengatasi tantangan ini dan memanfaatkan faktor pendukung yang tersedia, preseptor dapat meningkatkan kontribusinya dalam membentuk kompetensi klinis mahasiswa secara holistik. Kesimpulannya, mengoptimalkan peran preseptor sangat penting untuk mendukung pengembangan kompetensi klinis yang lebih komprehensif pada mahasiswa keperawatan.